The Dynamics of Islamic Political Parties Amid Indonesian Multicultural Society (State Islamic Institute of Kudus (IAIN Kudus), 2020)
Islam is not limited to religion that only talks about God. Islam has a comprehensive concept in all aspects of life, one of the aspect is politics (siyasa) that discusses the concept of the state, the exercise of power, who deserves to exercise power, how much power they can have, and the characteristics and objectives of Islamic politics itself. Political party is a superstructure in a political system that carries out several strategic functions, including political socialization, political recruitment, political articulation and aggregation of interests. Political party also has an important position in the policy making process. This paper aims to analyze how the dynamics of Islamic politics in Indonesia in the middle of multicultural society by carrying out its function as an articulator and aggregator of interests.